Development of LKS Model 5e in SPLDV Material to Improve Mathematical Communication of Class VIII Students - Ardina, Fimmatur Rizka (JMEA : Journal of Mathematics Education and Application, 2020)
This study aims to produce and describe the process of prototyping student worksheets using the 5E model in the SPLDV material to improve valid, practical and effective written mathematical communication skills of students of class VIII SMP. This type of research is development research that focuses on product development, namely LKS. The indicator of written mathematical communication skills in this study consists of four things, namely 1) students write mathematical ideas using mathematical language clearly so that they can be understood by others 2) students can write down the reasons for the answers given 3) students understand other people's thoughts by being able to restate other people's ideas in written form with their own sentences 4) students write down their responses (criticism and suggestions) to other people's ideas. The learning model used to make this worksheet is the 5E model which includes five phases, namely: engage, explore, explain, elaborate and evaluate. While the research model used is the Plomp research model which consists of three stages, namely preliminary research, prototyping phase, and assessment phase. The results of this study are in the form of a 5E model worksheet which has quality in terms of validity, practicality and effectiveness. In terms of validity, this worksheet is valid, namely in the good category. In terms of practicality, this worksheet is practical with the category of very good practicality. As for effectiveness, this LKS was effective with good effectiveness category.